IMPLEMENTASI KEBIJAKAN KETENAGAKERJAAN (Studi Kasus Pelatihan Kerja Bidang Otomotif pada Unit Pelaksana Teknis Pelatihan Kerja Kabupaten Bandung) - Rela Restu Widia (Jurnal Sosial Politik Unla, 2019)
This Research is motivated by the lack of optimal Implementation of employment policies case study of automotive training at UPT work training in Bandung District. Based on the background of the study, the following problems can be identified: How to Implementation of employment policies of automotive training at UPT work training in Bandung District, Inhibiting and supporting Factors for Implementation of employment policies of automotive training at UPT work training in Bandung District and the efforts made in implementation of employment policies of automotive training at UPT work training District. The theory in this study as an approach is the policies implementation theory put forward by Jones (1996) in Agustino (2016:154-155) with the dimensions Policy implementation that is organization, interpretation and application. Proposition submitted in this study are the Implementation of employment policies case study of automotive training at UPT work training in Bandung District, will be optimal if the implementation of the policy of employment training for automotive work at UPT Work training in Bandung District trough the approach suggest organizational, step interpretations and application. Inhibiting and supporting insfrastructure in the job training process, and socialization from UPT Work training to be more maximized so that every community can take part in job training programs implementtaion of employment policies case study of automotive training will optimally if there is a serious effort from government in the implementation of job training at UPT Work training in Bandung District. The method used is to use descriptive qualitative research methods. Data obtained through literature study participant.this research observation was carried out UPT Work training in Bandung District, when conducting interviews researches to colect data using tools such as recorder and digital camera. Based on the results of the study, that implementation of employment policy of automotive training at UPT work training in Bandung District is not optimal because it does not implementation Organization, interpretation and application.